Konsensus der Deutschsprachigen Arbeitsgemeinschaft für Mikrochirurgie der peripheren Nerven und Gefäße (DAM) für Mindeststandards mikrochirurgischer Trainings- und Übungskurse zur Vergabe eines Qualitätssiegels: Qualitätssiegel der DAM für mikrochirurgische Trainings- und Übungskurse = Consensus of the German-speaking Society for Microsurgery of Peripheral Nerves and Vessels (DAM) on minimum standards for microsurgical training courses and accreditation : minimum standards for microsurgical training courses and accreditation - Hirche, Christoph; Megerle, Kai Oliver; Heitmann, Christoph; Rois, Johannes; Russe, Friedrich; Froschauer, Stefan Mathias; Lehnhardt, Marcus; Kneser, Ulrich; Schaefer, Dirk J.; Kremer, Thomas (Handchirurgie, Mikrochirurgie, plastische Chirurgie, 2019)
Microsurgical training courses are an integral part of surgical education and training. Due to the changes in the surgical everyday routine, the competence and skills training outside the operating room has an increasingly important status. Multi-day, hands-on exercises with different models of increasing difficulty use artificial, avital and vital microsurgical models. The skills are evaluated with regard to fine motor skills as well as orientation in space and low-tremor motion sequences as well as bimanual manipulation exercises by means of "lobal rating scales". However, with numerous course offerings in German-speaking countries, there are no uniform and transparent contents and evaluation standards to reflect the quality of the courses. At a consensus meeting, minimum requirements for the contents of microsurgical training courses in the context of continuing medical education were defined and drafted as a German-language consensus in order to award a DAM quality seal. The parameters include the definition of targets, the existence of a scripts, the number of hours used, models used, practical exercise time on the microscope, trainer to participant ratio, types of anastomosis or coaptation (artery, vein, nerve, lymph vessel), application of a global rating scale , examination (grade/passed - failed), participant certificate and course evaluation. With the aim to meet the available courses/course concepts to maintain or improve the quality of education and training, the assignment of a "Basic" and an "Advanced" quality seal has been defined. The further stepwise development of the courses is necessary to sustain all skills and competencies for future microsurgeons. Integration of validated microsurgical simulators may reduce animal use and thus contribute to the ethical responsibility. The introduction of quality seals for microsurgical training courses should strengthen the transparency and commitment of participants and provide support to course providers with appropriately substantiated content through DAM.